On children as syncretic natives: Disrupting and moving beyond normative binaries. (September 2013) - Souto-Manning, Mariana
Historically, US schools have failed multicultural and multilingual children of colour and marginalized expansive conceptualizations of home and community literacy practices. Given the importance of fully inclusive education, this article seeks to understand the ways in which young multilingual and multicultural children take up issues of educational success and inclusion through translinguistic oral narratives. Through the analysis of a representative narrative authored by an Afro-Latino boy within the context of an afterschool programme, I introduce the notion of children as syncretic natives, intentionally and skilfully navigating within and across normative binaries set up by teachers who often occupy the role of syncretic immigrants. Because of a lack of support through professional development, teacher education and/or the ideologies promoted in school systems, many teachers tend to stick to a menu of known pedagogical practices and tools, taking on the role of syncretic immigrants as they implement and enforce normative binaries as opposite and exclusionary educational practices. As syncretic natives, children tend to engage in the creation of new practices, which move beyond traditional normative binaries. Findings indicate incoherencies in the construction of normative educational binaries and what counts as educational success. Implications point to the need for teachers to learn how to disrupt and move beyond normative binaries in order to see the brilliant syncretic practices of young children from multicultural and multilingual backgrounds, thus fashioning more fully inclusive curricula and teaching with the acknowledgement and recognition that children are syncretic natives who bring knowledge and expertise that can greatly enrich classroom opportunities for them to learn and grow.